Osteomodulin modulates the inflammatory responses via the interleukin-1 receptor 1/nuclear factor-κB signaling pathway in dental pulpitis - Yueyi Yang; Xuchen Hu; Meiling Jing; Xiaohan Zhu; Xiaoyu Liu; Wenduo Tan; Zhanyi Chen; Chenguang Niu; Zhengwei Huang (International Journal of Oral Science)
Abstract Pulpitis is a common infective oral disease in clinical situations. The regulatory mechanisms of immune defense in pulpitis are still being investigated. Osteomodulin (OMD) is a small leucine-rich proteoglycan family member distributed in bones and teeth. It is a bioactive protein that promotes osteogenesis and suppresses the apoptosis of human dental pulp stem cells (hDPSCs). In this study, the role of OMD in pulpitis and the OMD-induced regulatory mechanism were investigated. The OMD expression in normal and inflamed human pulp tissues was detected via immunofluorescence staining. Intriguingly, the OMD expression decreased in the inflammatory infiltration area of pulpitis specimens. The cellular experiments demonstrated that recombined human OMD could resist the detrimental effects of lipopolysaccharide (LPS)-induced inflammation. A conditional Omd knockout mouse model with pulpal inflammation was established. LPS-induced inflammatory impairment significantly increased in conditional Omd knockout mice, whereas OMD administration exhibited a protective effect against pulpitis. Mechanistically, the transcriptome alterations of OMD overexpression showed significant enrichment in the nuclear factor-κB (NF-κB) signaling pathway. Interleukin-1 receptor 1 (IL1R1), a vital membrane receptor activating the NF-κB pathway, was significantly downregulated in OMD-overexpressing hDPSCs. Additionally, the interaction between OMD and IL1R1 was verified using co-immunoprecipitation and molecular docking. In vivo, excessive pulpal inflammation in Omd-deficient mice was rescued using an IL1R antagonist. Overall, OMD played a protective role in the inflammatory response via the IL1R1/NF-κB signaling pathway. OMD may optimize the immunomodulatory functions of hDPSCs and can be used for regenerative endodontics.